Refleksi Peran Mahkamah Konstitusi Dalam Penyelesaian Sengketa Pemilihan Umum 2004 - Sri Hastuti Puspitasari (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The changes of UUD 1945 has an implication on the establishment of Constitution Justice. One of the authorities of the institution whose authority is in the same line with Supreme Court is the dispute settlement of General Election results. The role played by Constitution Justice, once it solved the dispute of the result of general election in 2004, proved that the principals of court justice have been implemented in order to keep the democracy and to establish the constitution.